If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2y + 3 = -4y + -5 Reorder the terms: 3 + -2y = -4y + -5 Reorder the terms: 3 + -2y = -5 + -4y Solving 3 + -2y = -5 + -4y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '4y' to each side of the equation. 3 + -2y + 4y = -5 + -4y + 4y Combine like terms: -2y + 4y = 2y 3 + 2y = -5 + -4y + 4y Combine like terms: -4y + 4y = 0 3 + 2y = -5 + 0 3 + 2y = -5 Add '-3' to each side of the equation. 3 + -3 + 2y = -5 + -3 Combine like terms: 3 + -3 = 0 0 + 2y = -5 + -3 2y = -5 + -3 Combine like terms: -5 + -3 = -8 2y = -8 Divide each side by '2'. y = -4 Simplifying y = -4
| -5x+6y=120 | | -0.7x+2.69=-0.5x+3.49 | | 4x-3=x-2 | | 2x-8x+10/2x | | 20y^4-125y^2=0 | | -x^2+6x+1=0 | | (6+j)-(3-4j)= | | 5q/10d+15q | | 2x-y=-20 | | 4.4x-23=2.4x+7 | | 2n+3/8n^2+4+n-3/8n^2+4n | | 20-4x=25-5x | | h-=? | | 0.2x+0.7=-0.9 | | 3(x-9.2)=3.6 | | y=-(x+4) | | -6y=3.84 | | 45-2m=15+3m | | 4(4x+3)=7(x-2)+10 | | f(x)=2(22)-5 | | 36ab^2-48a^2b= | | 0.7x+14.7=x-2.16 | | -36+38= | | f(x)=1.5(1.1)+7.6 | | y=3x^5+4x^3+2x | | 5+8*9= | | 15xy+30x^2y^2= | | 4*5-4= | | 4x=y-6 | | 0.7x+14.7=-2.16 | | 3x^3-2=0 | | 3y+5y=10y-18 |